The Relationship Between Reading Strategy and Reading Comprehension: A Meta-Analysis - Sun, Yuanke; Wang, Jindao; Dong, Yang; Zheng, Haoyuan; Yang, Jie; Zhao, Yaman; Dong, Weiyang (Frontiers in Psychology, 2021)
This study synthesized the correlation between four categories’ reading strategy and reading comprehension based on Weinstein and Mayer’s reading strategy model. The current meta-analysis obtained 57 effect sizes which represented 21548 readers, and all selected materials came from empirical studies published from 1998 to 2019. Results showed all four categories’ reading strategy had similar correlation effect size with reading comprehension. The correlation between monitoring strategy and reading comprehension was significantly larger in first language scripts than second language scripts. Affective strategy and elaboration strategy had an independent effect on reading comprehension which was not significantly moderated by selected moderators. Results suggested that all four categories’ reading strategy may have a similar contributions to text comprehension activities.